Role of the GalNAc-galectin pathway in the healing of premature rupture of membranes - Jia-Le Chen; Lou Liu; Xin-Rui Peng; Yan Wang; Xiang Xiang; Yu Chen; De-Xiang Xu; Dao-Zhen Chen (BMC, 2024)
Abstract Background Premature rupture of the membranes (PROM) is a key cause of preterm birth and represents a major cause of neonatal mortality and morbidity. Natural products N-acetyl-d-galactosamine (GalNAc), which are basic building blocks of important polysaccharides in biological cells or tissues, such as chitin, glycoproteins, and glycolipids, may improve possible effects of wound healing. Methods An in vitro inflammation and oxidative stress model was constructed using tumor necrosis-α (TNF-α) and lipopolysaccharide (LPS) action on WISH cells. Human amniotic epithelial cells (hAECs) were primarily cultured by digestion to construct a wound model. The effects of GalNAc on anti-inflammatory and anti-oxidative stress, migration and proliferation, epithelial-mesenchymal transition (EMT), glycosaminoglycan (GAG)/hyaluronic acid (HA) production, and protein kinase B (Akt) pathway in hAECs and WISH cells were analyzed using the DCFH-DA fluorescent probe, ELISA, CCK-8, scratch, transwell migration, and western blot to determine the mechanism by which GalNAc promotes amniotic wound healing. Results GalNAc decreased IL-6 expression in TNF-α-stimulated WISH cells and ROS expression in LPS-stimulated WISH cells (P < 0.05). GalNAc promoted the expression of Gal-1 and Gal-3 with anti-inflammatory and anti-oxidative stress effects. GalNAc promoted the migration of hAECs (50% vs. 80%) and WISH cells through the Akt signaling pathway, EMT reached the point of promoting fetal membrane healing, and GalNAc did not affect the activity of hAECs and WISH cells (P > 0.05). GalNAc upregulated the expression of sGAG in WISH cells (P < 0.05) but did not affect HA levels (P > 0.05). Conclusions GalNAc might be a potential target for the prevention and treatment of PROM through the galectin pathway, including (i) inflammation; (ii) epithelial-mesenchymal transition; (iii) proliferation and migration; and (iv) regression, remodeling, and healing.